Encapsulation of quaternary 1D pentlandite-type alloy crystals within conical multi-layer carbon nanotubes. - Costa, P; Sloan, J; Hutchison, J; Green, M (2003)
Ordered 1D crystals of a complex pentlandite-type alloy with the general composition (Fe,Ni,Co)9S8 have been synthesised inside conical Multi Walled Carbon Nanotubes (MWNTs); the crystals are observed as a by-product of an arc-evaporation synthesis of Double Walled Carbon Nanotubes (DWNTs).